Optimalisasi Prinsip Lā Ḍarar wa Lā Ḍirār dalam Akad Mudarabah: Studi Kasus Praktik Bisnis Mizuta di Makassar - Wahyuni Nur, Sri Reski; Saadal Jannah; Nabilah Al Azizah; Shaimah Azzahar (AL-KHIYAR: Jurnal Bidang Muamalah dan Ekonomi Islam, 2024)
The practice of mudarabah is often a topic of debate, particularly when mudarabah financing involves capital contributions from the mudarib. Therefore, it is necessary to find solutions to the issues within the mudarabah contract by applying fiqh principles. This study aims to understand the concept of the mudarabah contract in Islam and its relation to the principle of lā ḍarar wa lā ḍirār. The research questions addressed are: first, how does the concept of the mudarabah contract in Islam relate to the principle of lā ḍarar wa lā ḍirār? Second, how is the principle of lā ḍarar wa lā ḍirār implemented in mudarabah partnerships in Mizuta Makassar?. This research employs a qualitative method with normative and sociological approaches, and it is conducted as field research. The findings reveal: firstly, in the mudarabah contract, the ṣāḥibu al-Māl, as the capital owner, entrusts all their assets to the mudarib, who manages these assets under the condition that the profit is shared according to the initial agreement. In practice, there is often injustice between the parties involved, which necessitates the application of the principle of lā ḍarar wa lā ḍirār to prevent harm. Secondly, in Mizuta Makassar, the principle of lā ḍarar wa lā ḍirār is implemented through the establishment of a clear contract from the outset, transparency in reporting, and regular evaluation meetings. To date, this approach has successfully prevented disputes within the partnership. The implications of this study are expected to serve as a reference for other researchers in similar studies and to further develop research in this field.